The Role of Gratitude in the Resilience of Mothers Who Have Children with Autism Spectrum Disorders - Daulay, Dira Anisah Ulfah; Sutatminingsih, Raras; Siregar, Ade Rahmawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The resilience of mothers who have children with autism spectrum disorders in Indonesia has not been studied quantitatively. It is important to study because it is linked to the variable gratitude for resilience in mothers who have children with autism spectrum disorders. This research was carried out in the city of Medan in places that have mothers of children with autism spectrum disorders, such as special schools (SLB), both public and private, therapy places, or paediatrician clinics. In this research, the sampling technique used was non-probability sampling. Gratitude plays a positive and significant role in resilience in mothers who have children with autism spectrum disorders. Most research subjects had a high sense of gratitude and resilience, totalling 47 people. Subjects who had high feelings of gratitude with moderate resilience were 42, subjects who had moderate feelings of gratitude and moderate resilience were eight people, subjects who had moderate gratitude with low resilience were four people, subjects who had moderate gratitude with high resilience were two people, and subjects who had high gratitude with low resilience were one person.